Surgical treatment of isolated fistulae of coronary arteries - Porto,Jorge Alberto Monteiro (2003)
OBJECTIVE:To report the surgical results obtained with the surgical correction of fistulae of coronary arteries in the pulmonary artery branch. METHOD: From 1995 to 1999, three female patients with diagnoses of isolated fistulae of coronary arteries confirmed by cinecoronariography underwent surgery. RESULTS: No other associated heart diseases were observed in the patients. The main symptom of all patients was angina pectoris. After closing the coronary fistulae the patients progressed with event-free post-operative periods and with total recovery from the angina. CONCLUSION: Surgical treatment should be considered for all patients diagnosed as having isolated fistulae, due to the low morbid-mortality rate in addition to the technical simplicity of closing and performing the ligature of fistulae.